Asset Pricing in Economies with Frictions - Luttmer, Erzo G. J. (Econometrica, 1996)
This paper examines how proportional transaction costs, short-sale constraints, and margin requirements affect inferences based on asset return data about intertemporal marganil rates of substitution (IMRSs). Small transaction costs greatly reduce the required variability of IMRSs, suggesting that the low variability of many parametric, aggregate consumption based IMRSs need not be inconsistent with asset return data. Euler inequalities for a transaction cost economy with power utility are tested using aggregate consumption data and returns on stocks and U.S. Treasury bills. In the majority of cases, there is little evidence against power utility specifications with a low risk-aversion parameter. Copyright 1996 by The Econometric Society.